Zealactones. Novel natural strigolactones from maize. (May 2017) - Charnikhova, Tatsiana V.; Gaus, Katharina; Lumbroso, Alexandre; Sanders, Mark; Vincken, Jean-Paul; De Mesmaeker, Alain; Ruyter-Spira, Carolien P.; Screpanti, Claudio; Bouwmeester, Harro J.
Abstract: In the root exudate and root extracts of maize hybrid cv NK Falkone seven putative strigolactones were detected using UPLC-TQ-MS-MS. All seven compounds displayed MS-MS-fragmentation common for strigolactones and particularly the presence of a fragment of m/z 97 Da, which may indicate the presence of the so-called D-ring, suggests they are strigolactones. The levels of all these putative strigolactones increased upon phosphate starvation and decreased upon fluridone (carotenoid biosynthesis inhibitor) treatment, both of which are a common response for strigolactones. All seven compounds were subsequently isolated with prep-HPLC-MS. They all exhibited Striga hermonthica seed germination inducing activity just as the synthetic strigolactone analog GR24. The structure of two of the seven compounds was elucidated by NMR spectroscopy as: methyl (2E, 3E)-4-(3, 3-dimethyl-5-oxo-2-(prop-1-en-2-yl)tetrahydrofuran-2-yl)-2-(((4-methyl-5-oxo-2, 5-dihydrofuran-2-yl)oxy)methylene)but-3-enoate (two diastereomers1a and1b ). Strigolactones (1a/b) are closely related to the methyl ester of carlactonoic acid (MeCLA) and heliolactone. However, they contain a unique 4, 4-dimethyltetrahydrofuran-2-one motif as the "A-ring" instead of the classical (di)methylcyclohexene. Because these compounds were isolated from maize ( Zea mays ) we called them "zealactone 1a and 1b". The implications of this discovery for our view on strigolactones and their biosynthesis are discussed. Graphical abstract: Highlights: In maize root exudate 7 putative strigolactones were detected using UPLC-TQ-MS-MS. They were isolated and exhibited Striga seed germination inducing activity. The structure of two of these compounds was elucidated by NMR spectroscopy. They have an A-ring different from other strigolactones and are coined zealactones. The implications for our view on strigolactones and their biosynthesis are discussed.